Hi!(adsbygoogle = window.adsbygoogle || []).push({});

I wondered if there is possible to get an explanation of the "Law of mass action." Here is a simple derivation:

eq.1 aA + bB = cC + dD

eq.2 R(f)= k(f)[A]^a*^b

eq.3 R(b)= k(b)[C]^c*[D]^d

eq.4 At equilibrium R(f)=R(b)

eq.5 k(e)=k(f)/f(b)=([C]^c*[D]^d)/([A]^a*^b)

Well, if a=4 and b=3, the left side of eq.1 becomes:

eq.6 {left side}= 4A + 3B

eq.7 {left side}= A + A + A + A + B + B + B

Now (this is probably a pretty stupid question), why is it that all the factors in eq.2-5 are *multiplied* together, and not *added*?

**Physics Forums - The Fusion of Science and Community**

# The Law of Mass Action explained

Have something to add?

- Similar discussions for: The Law of Mass Action explained

Loading...

**Physics Forums - The Fusion of Science and Community**